2012
DOI: 10.2166/wh.2012.028
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood pressure and metabolic syndrome components with magnesium levels in drinking water in some Serbian municipalities

Abstract: Chronic exposure to insufficient levels of magnesium (Mg) in drinking water increases the risk of magnesium deficiency and its association with hypertension, dyslipidemia and type 2 diabetes mellitus. The aim of the study was to assess the potential association of mineral contents in drinking water with blood pressure and other components of metabolic syndrome (MetS) (BMI as measure of obesity, triglycerides, glucose, and insulin resistance, index-HOMA IR), in a healthy population. This study was conducted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
1
16
0
2
Order By: Relevance
“…Many studies have documented the association of serum Mg concentrations and endothelial function [30, 31]. Low Mg in drinking water is found to be associated with cardiometabolic risk factors [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have documented the association of serum Mg concentrations and endothelial function [30, 31]. Low Mg in drinking water is found to be associated with cardiometabolic risk factors [32]. …”
Section: Discussionmentioning
confidence: 99%
“…It may have a positive effect on blood pressure, as reflected by the comparison of individuals from some Serbian municipalities having different drinking water Mg(II) concentrations. This comparison showed that diastolic blood pressure was the lowest in subjects from the district with the highest drinking water Mg(II) concentration (42 mg/L, compared to 11 mg/L) [10]. Low levels of magnesium in drinking water can aggravate liver damage from alcohol [11].…”
Section: Health Risks Associated With Low Mg(ii) Concentrations In Drmentioning
confidence: 95%
“…Existen también estudios que muestran que tanto ingestas defi citarias como niveles plasmáti-cos bajos de magnesio aumentan la prevalencia de muerte súbita 64 . Asimismo, los bajos niveles de magnesio se asociaron con la presencia de HTA y también con alteraciones en la estructura vascular 65,66 . Asimismo, se ha descripto que los productos y las aguas que contienen mayor cantidad de magnesio producen una reducción de la enfermedad coronaria, particularmente una mayor ingesta de magnesio reduce los eventos coronarios fatales 51,67 .…”
Section: ¿Cómo Infl Uyen Los Otros Minerales Presentes En Las Aguas Nunclassified